Cerebral hypoperfusion is not associated with an increase in amyloid β pathology in middle‐aged or elderly people. Issue 1 (15th July 2017) - Hansson, Oskar; Palmqvist, Sebastian; Ljung, Hanna; Cronberg, Tobias; van Westen, Danielle; Smith, Ruben
Abstract: Introduction: It is hypothesized that cerebral hypoperfusion promotes the development of Alzheimer pathology. We therefore studied whether longstanding cerebral hypoperfusion is associated with Alzheimer pathology in nondemented humans. Methods: Cerebral blood flow and amyloid β ( 18 F‐Flutemetamol) positron emission tomography retention were assessed in eleven patients with unilateral occlusion of precerebral arteries resulting in chronic and uneven hypoperfusion. A subset of patients underwent tau ( 18 F‐AV‐1451) positron emission tomography. Results: The blood flow was significantly reduced on the affected side of the brain in patients with unilateral occlusion of the internal carotid artery or stenosis of the middle cerebral artery. However, the cortical uptake of 18 F‐Flutemetamol or 18 F‐AV‐1451 was not altered. Discussion: Our results suggest that longstanding cerebral hypoperfusion in humans does not result in accumulation of amyloid β fibrils or tau aggregates.